Custom Ocular Prosthesis for Enucleated Eye: A Case Report - Pun, Surya Narayan; Shakya, Rojina; Adhikari, Galav; Parajuli, Prakash Kumar; Singh, Raj Kumar; Suwal, Pramita (Journal of College of Medical Sciences-Nepal, 2016)
The unfortunate loss or absence of an eye may be caused by a congenital defect, irreparable trauma, tumor, sympathetic ophthalmia, or the need for histologic confirmation of a suspected diagnosis. Early rehabilitation with suitable prosthesis is recommended to ease the mind of the afflicted. An ocular prosthesis is a maxillofacial prosthesis that artificially replaces an eye missing as a result of trauma, surgery, or congenital absence. A custom ocular prosthesis has advantage of close adaptation to the tissue bed, provides maximum comfort and restores full physiological function to the accessory organs of the eye.